The Tragedy Of Love And Exile In ‘’Qashidah Nuniyyah’’ By Ibn Zaydun: A Semiological Analysis By Roland Barthes - Nafidzah Hishosul Abawani; Khomisah Khomisah; Ihin Solihin (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study addresses the problem of how the tragedy of love and exile in Qasidah Nūniyyah by Ibn Zaydun is constructed as a system of meaning that operates not only emotionally but also ideologically. Previous studies have predominantly emphasized its aesthetic and romantic dimensions, leaving its symbolic and mythological structures insufficiently explored. Therefore, this research aims to analyze the construction of tragic love and exile through the semiological framework of Roland Barthes, particularly his three levels of signification: denotation, connotation, and myth. Employing a qualitative descriptive method with textual analysis, this study examines selected verses containing major symbols such as night, tears, longing, fire, and exile. The findings indicate that at the denotative level, these symbols refer to literal experiences of separation and displacement. At the connotative level, they represent psychological suffering and identity fragmentation. At the mythological level, however, tragedy is naturalized as a process of spiritual purification and moral legitimation, where suffering becomes a sign of loyalty and dignity. The contribution of this research lies in demonstrating the applicability of Barthesian semiology to classical Arabic literature and revealing the ideological dimension embedded within Andalusian poetic symbolism.